KAJIAN GREEN CONSTRUCTION STUDI KASUS: PERUMAHAN BERANDA BALI - Hizkia Kurniawan Tarigan; Jati Utomo Dwi Hatmoko; Frida Kistiani (Jurnal Karya Teknik Sipil, 2013)
The construction is part of the largest contributor to emissions of CO2. The concept of green construction  is one of the business that can minimize negative impact on the environment in the process of construction . The research objective are to analyze and to evaluate the application of green construction on housing development of Beranda Bali by PT Mikroland Property Development. The methods used in this study is interviews , observation , and documentation. It is done by observing the application of green construction approaches with the underlying indicator of planning and scheduling, resource and material cycles, protection, waste management, construction, material storage, manifesting a work place eco friendly, the selection and operation of construction tools, training for sub contractor, air quality, documentation, health and convenience, environmental, management project the reduction of the ecological, foot print, water conservation, land use, energy efficiency and conservation in the green construction factors. The data processing is done by comparing the results of the research data with factors of green construction in PT.Pembangunan Perumahan, Green Building Council Indonesia (2012). The results obtained are there are 10 applications have been applied by PT Mikroland Property Development which include planning and schedulling, resource and material cycle, the protection of job sites, construction waste management, material storage, manifesting a work place eco friendly, water conservation, the reduction of the ecological foot print, appropriate land use, energy efficiency and conservation. Thus Perumahan Beranda Bali has applied the concept of green construction of 60% of the 17 application of the factors that affect the construction of green